PROMOTING CRITICAL THINKING AND ENGAGEMENT THROUGH DIGITAL AND MEDIA LITERACY IN HIGHER EDUCATION - Inayah, Ratih; Sakhiyya, Zulfa; Widhiyanto, Widhiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
In the digital era, the ability to engage with digital technologies and media critically is essential for student success in higher education. Digital and media literacy (DML) equips learners with the necessary skills to access, analyze, evaluate, and create content across platforms while engaging responsibly in digital environments.Although the urgency of DML integration is widely acknowledged, research shows a lack of comprehensive, interdisciplinary implementation in university curricula and limited attention to how DML supports critical thinking and student engagement. This paper aims to explore how digital and media literacy can be strategically implemented in higher education to foster students’ critical thinking and meaningful academic engagement.This study adopts a qualitative, content-based approach by analyzing current frameworks and synthesizing insights from scholarly literature on digital pedagogy. Findings suggest that embedding DML across disciplines using instructional design models like TPACK and ADDIE, employing collaborative tools such as Padlet and Canva, and promoting ethical media analysis can enhance critical thinking. Key barriers include inequitable access and insufficient educator training. Effective DML integration can transform higher education by preparing students for academic, professional, and civic life in the digital age.